2021
DOI: 10.1177/20503121211059682
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid awareness and usage among females at Saudi Electronic University in Jeddah, Saudi Arabia

Abstract: Objectives: This study evaluates awareness of folic acid and neural tube defects, use of folic acid and knowledge of folic acid usage among female university students in Saudi Arabia. Methods: An analytical cross-sectional survey was conducted in the Jeddah branch of Saudi Electronic University. A total of 400 female students in the 19–45 years age group were contacted to participate in the study using a convenience sampling method. Eighty-eight students refused to participate, so 312 students were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Studies from Saudi Arabia showed similar results with knowledge of FA reported from 55.7% to as much as 90% [ 16 , 17 , 18 , 19 ]. Saudi Arabian studies also revealed that a higher level of education, specialization in health sciences and being married were factors for awareness, knowledge and use of FA [ 16 , 18 ]. Furthermore, a study showed that older women have the tendency to not use FA supplementation [ 19 ].…”
Section: Introductionsupporting
confidence: 77%
“…Studies from Saudi Arabia showed similar results with knowledge of FA reported from 55.7% to as much as 90% [ 16 , 17 , 18 , 19 ]. Saudi Arabian studies also revealed that a higher level of education, specialization in health sciences and being married were factors for awareness, knowledge and use of FA [ 16 , 18 ]. Furthermore, a study showed that older women have the tendency to not use FA supplementation [ 19 ].…”
Section: Introductionsupporting
confidence: 77%
“…The high awareness in these two studies was due to good information disseminated by doctors and nurses, while in the current study hearing about folic acid from a medical practitioner displayed a negative relation with participants' knowledge. 16 Al-Mohaithef et al, in Jeddah showed similar findings with the current where a majority heard of folic acid, but a smaller number of females knew about neural tube defects, while a bachelor's degree and married status were associated with better knowledge. 17 Raad et al, reported low knowledge among Saudi women, regarding sources of folic acid and its generic name which differs from our findings but like…”
Section: Discussionmentioning
confidence: 62%
“…Females who were younger than 18 or older than 50 years and belonging to medical and paramedical fields were excluded from the study An . English questionnaire was designed by the researchers after going through published studies [14][15][16][17][18] and literature in depth.…”
Section: Methodsmentioning
confidence: 99%
“…However, there's a lack of studies investigating MVMM usage among Saudi Arabia's population and the factors related to it. Furthermore, most studies focused only on one or two dietary supplements [14][15][16], disregarding MVMM usage, which is what this study is targeting. Our study of 310 participants showed a significant positive relationship between MVMM usage with gender and employment status.…”
Section: Discussionmentioning
confidence: 99%